Non-financial hurdles for human capital accumulation: Landownership in Korea under Japanese rule - Bogang Jun; Tai-Yoo Kim (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2014)
This paper suggests that inequality in landownership is a non-financial hurdle for human capital accumulation. It is the first to present evidence that inequality in landownership had an adverse effect on the level of public education in the Korean colonial period. Using a fixed effects model, the present research exploits variations in inequality in land concentration across regions in Korea and accounts for the unobserved heterogeneity across these regions. The analysis establishes a highly significant adverse effect of land inequality on education in the Korean colonial period.
urn:nbn:de:bsz:100-opus-10266
Keywords: I25; N35; Q15; 330; Land inequality; Education; Development; Korean economic history